Design, docking, synthesis and anti-E. coli screening of novel thiadiazolo thiourea derivatives as possible inhibitors of Enoyl ACP reductase (FabI) enzyme - George, Sonia; Ramzeena, Mohammed Basheer; Ram, Sayee Vignesh; Selvaraj, Senthil Kumar; Rajan, Shinu; Ravi, Thengungal Kochupappy (Bangladesh Journal of Pharmacology, 2014)
A series of 1-phenyl-[5-substitutedphenyl)-1,3,4-thiadiazol-2-yl]-3-thiourea (3a-h) were synthesized and screened for their anti Escherichia coli potential. The characterization of the newly synthesized compounds was based upon their spectral data. The design of the title compounds was done utilizing the in silico methodology. Virtual screening technique was utilized for the identification of the lead, thiadiazole. The pharmacokinetic behavior was predicted by lead optimization and docking studies helped to analyze the binding interactions. Antibacterial activity of the title compounds were predicted by the PASS prediction software. The anti E. coli screening results showed that the derivatives, 3b and 3h possessed significant activity.